If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 17 = -7 Reorder the terms: 17 + 9x = -7 Solving 17 + 9x = -7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + 9x = -7 + -17 Combine like terms: 17 + -17 = 0 0 + 9x = -7 + -17 9x = -7 + -17 Combine like terms: -7 + -17 = -24 9x = -24 Divide each side by '9'. x = -2.666666667 Simplifying x = -2.666666667
| 8x+750=30x-650 | | C^2-4c= | | 4z=5z-18 | | 2a+3b=83 | | 2p^3q^2+p^2q+pq= | | 8(v+2)-4v=2(2v+1)-11 | | -3m=j-18 | | 13s-19s=18 | | 3y^2+8=36 | | 9y+9=8y-8 | | -5x+34x+7= | | 67n=-22 | | 2p^3+p^2q+pq= | | -5p+2+6p=9 | | -694=.83r | | 2x^2+27x-5.1=0 | | -.125x=-4 | | .1b=-108 | | 3(4z-1)-5(z+1)=3(z+1) | | 3y-12=7 | | .05=.6m | | 3x^2+4+1= | | -.75k=.67 | | -13x^3+20x-7=0 | | 18=-.5t | | -4d+2(4+9)=-14 | | 0.083n=12 | | 9m-13=-22+8m | | 36y=108 | | x^3-x^2-1120=0 | | x=-3y^2-12y | | 3(x-4)-2(x+2)-13=-20 |